Fulfillment of the Rights of Children with Special Needs: A Positive Law and Islamic Law Perspective - A Case Study in West Java - Fatriany, Fenny; Mayaningsih, Dewi (Jurnal Multidisiplin West Science, 2024)
This study aims to analyze the fulfillment of the rights of children with special needs (ABK) from the perspectives of positive law and Islamic law, as well as to identify the challenges encountered in its implementation. The research uses a normative juridical approach with a descriptive-analytical method, combining the analysis of laws and regulations, legal theory, and the concept of Sharia. Data collection techniques include literature study, observation, and interviews with relevant parties. The results show that both positive law and Islamic law emphasize the importance of protection and fulfillment of ABK rights, including rights to education, health, and non-discriminatory treatment. However, significant challenges are found in implementation, such as social stigma, lack of facilities, and low public awareness. Other obstacles include limited government budget allocation and inadequate infrastructure in various regions. This study recommends improving public education, fostering synergy among stakeholders, and providing inclusive facilities to ensure the optimal fulfillment of ABK rights.